Analisis Aneksi dengan kata Kerja Rubrik Opini pada Kumparan.com sebagai Modul Ajar Teks Deskripsi - Stevani Tistayulia Rodiah Sinaga; Hendra Setiawan; Dewi Suprihatin (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2025)
This study focuses on annexation with verbs. Annex is a branch of morphology. The purpose of this study is to analyze annex with verbs in the Kumparan.com opinion rubric, as part of the study of morphology, as a teaching module for descriptive text. This study used a qualitative method, with data on annexation with verbs in opinion articles from the April 2025 edition. Data analysis was conducted by analyzing each article in the Kumparan.com opinion rubric. The object of this study was the process of forming annexation with verbs in the Opinion & Stories rubric. Based on the results of the study, it can be concluded that there is a relationship between the process of forming annexation with verbs in opinion articles, namely the frequent occurrence of annex with verbs in opinion articles. Therefore, annexation with verb in the Kumparan.com opinion rubric are suitable for use as a teaching module for descriptive texts, which discuss the process of word formation, especially word dissolution.